Observations of the Ultraviolet-bright Star Y453 in the Globular Cluster M4 (NGC 6121) - Dixon, William V. (2017)
We present a spectral analysis of the UV-bright star Y453 in M4. Model fits to the star's optical spectrum yield Teff ∼ 56,000 K. Fits to the star's FUV spectrum, obtained with the Cosmic Origins Spectrograph on board the Hubble Space Telescope, reveal it to be considerably hotter, with Teff ∼ 72,000 K. We adopt Teff = 72,000 ± 2000 K and log g = 5.7 ± 0.2 as our best-fit parameters. Scaling the model spectrum to match the star's optical and near-infrared magnitudes, we derive a mass M∗ = 0.53±0.24 M⊙ and luminosity = log L/L⊙ 2.84±0.05, consistent with the values expected of an evolved star in a globular cluster. Comparing the star with post-horizontal-branch evolutionary tracks, we conclude that it most likely evolved from the blue horizontal branch, departing the asymptotic giant branch before third dredge-up. It should thus exhibit the abundance pattern (O-poor and Na-rich) characteristic of the second-generation (SG) stars in M4. We derive the star's photospheric abundances of He, C, N, O, Si, S, Ti, Cr, Fe, and Ni. CNO abundances are roughly 0.25 dex greater than those of the cluster's SG stars, while the Si and S abundances match the cluster values. Abundances of the iron-peak elements (except for iron itself) are enhanced by 1-3 dex. Rather than revealing the star's origin and evolution, this pattern reflects the combined effects of diffusive and mechanical processes in the stellar atmosphere.